Hukum Internasional tentang Genosida dalam Perspektif Fikih Dauly - Miftahuddini Ashar, Nimas Masrullail (al-Daulah: Jurnal Hukum dan Perundangan Islam, 2014)
Abstract: This article discusses about the genocide in international law on the dauliy jurisprudence perspective. International law governs the genocide crime in the Rome Statute which is applied for the state parties. The Rome Statute becomes the basis for the International Criminal Court (ICC) which is responsible for handling the case of genocide and other cases listed in the Rome Statute. Based on article 77 of the Rome Statute, genocide perpetrator will be liable to imprison of not more than 30 years, or a lifetime (under certain condition). In addition, the offender will be liable to fine and confiscation. Based on this, international law governing the genocide can be quite fair because there is no difference in the position of judge and imposing sanction, but when it is viewed from the dauliy jurisprudence perspective, sanction given to the perpetrator of genocide is considered not to be commensurate with the conducted crime.Keywords: Dauliy Jurisprudence, Genocide, International Law